2018
DOI: 10.1021/acs.inorgchem.7b02929
|View full text |Cite
|
Sign up to set email alerts
|

NOTA Complexes with Copper(II) and Divalent Metal Ions: Kinetic and Thermodynamic Studies

Abstract: Hnota derivatives are among the most studied macrocyclic ligands and are widely used for metal ion binding in biology and medicine. Despite more than 40 years of chemical research on Hnota, the comprehensive study of its solution chemistry has been overlooked. Thus, the coordination behavior of Hnota with several divalent metal ions was studied in detail with respect to its application as a chelator for copper radioisotopes in medical imaging and therapy. In the solid-state structure of the free ligand in zwit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 79 publications
(117 reference statements)
4
44
0
Order By: Relevance
“…NOTA has been well characterized as a thermodynamically and kinetically stable copper binding ligand suitable for conjugating to a variety of targeting groups. 18 An oligo-ethylene glycol linker was used to separate the ceragenin and NOTA to ensure that the bound copper ion did not interfere with interactions with bacterial membranes. In efforts to determine the structural features of conjugates 1 and 2 that impact bacterial labelling and imaging, structural variants 3 and 4 were prepared.…”
Section: Resultsmentioning
confidence: 99%
“…NOTA has been well characterized as a thermodynamically and kinetically stable copper binding ligand suitable for conjugating to a variety of targeting groups. 18 An oligo-ethylene glycol linker was used to separate the ceragenin and NOTA to ensure that the bound copper ion did not interfere with interactions with bacterial membranes. In efforts to determine the structural features of conjugates 1 and 2 that impact bacterial labelling and imaging, structural variants 3 and 4 were prepared.…”
Section: Resultsmentioning
confidence: 99%
“…If the pH was too low, 64 Cu flouts out from the Cu chelator complex decreasing the labeling yield. If the pH is too high, Cu(OH) 2 will be formed, and 64 Cu cannot efficiently coordinate with the chelators . A range of molar activity from 12 to 45 GBq/μmoL obtained for [ 64 Cu]Cu‐ 1 , [ 64 Cu]Cu‐ 2 , and [ 64 Cu]Cu‐ 3 was comparable with that for other 64 Cu‐labeled chelators or 64 Cu‐labeled bioconjugates .…”
Section: Discussionmentioning
confidence: 85%
“…For thermodynamic and kinetic reasons, H3NOTA and other NOTA derivatives are widely used carriers of copper radionuclides as they predominantly form the Cu 2+ complex over complexes with common impurities in radiochemical formulations, such as Zn 2+ and Ni 2+ . [52][53][54] As such, NOTA is an ideal receptor to trap Cu 2+ ions in a fast and practically irreversible way at low concentrations and potentially even in the presence of biologically more abundant Zn 2+ . Luminescent lanthanide complexes with carbostyril sensitizers are well known to possess high luminescence quantum yields, millisecond lifetimes and excellent stability in aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%
“…concomitant strong luminescence quenching effect, whereas no or only minor effects were observed with other cations(Figures 3 and 4). It was previously shown that the [Cu(NOTA)] − complex shows high thermodynamic stability (log K = 23.33) and fast quantitative formation, even at pH < 1.5 52. The NOTA ligand is very selective for Cu 2+ ions over alkali and earth alkali metal ions (log K = 2-5 and log K = 7-11, respectively) and moderately selective over other transition metal ions (e.g., log K (Mn 2+ ) = 16.30 and log K (Zn 2+ ) = 22.32) 52.…”
mentioning
confidence: 99%
See 1 more Smart Citation